Smart Contracts Contracts - Bartoletti, Massimo (Frontiers in Blockchain, 2020)
This paper explores the connection between software contracts and smart contracts. Despite the assonance, these two terms denote quite different concepts: software contracts are logical properties of software components, while smart contracts are programs executed on blockchains. What is the relation between them? We answer this question by discussing how to integrate software contracts in the design of programming languages for smart contracts.